The Effect of the Ease of Collection Rediscovery Through the Shelving System on Visitor Satisfaction - Salma, Siti Nurusysyifa; Rukajat, Ajat; Fatimah Az Zahro (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine the effect of ease of information retrieval through the shelving system on visitor satisfaction at the Library of the Ministry of Primary and Secondary Education. The research employed a quantitative approach, using observation, questionnaires, and documentation as data collection techniques. The sample consisted of 67 active library visitors selected as respondents. The collected data were analyzed using descriptive statistics and simple linear regression with the assistance of IBM SPSS version 27. The findings reveal that the shelving system has been implemented effectively, particularly in supporting the ease of retrieving collections. This is reflected in the systematic arrangement of materials based on the Dewey Decimal Classification (DDC), as well as the use of clear labels and classification codes that help users locate library resources more quickly and accurately. The level of visitor satisfaction is categorized as high, as indicated by the mean score, which demonstrates positive user perceptions regarding the ease of access, speed in finding materials, and efficiency in the information search process. Furthermore, the results of the regression analysis indicate that ease of information retrieval through the shelving system has a positive and significant effect on visitor satisfaction, with a significance value of 0.009 (< 0.05), a t-value of 2.706, and a regression coefficient of 0.349. These results suggest that improvements in the ease of retrieving collections will lead to higher levels of visitor satisfaction. Therefore, optimizing the shelving system is essential in enhancing the overall quality of library services.